Analysis of Fossil Pollen Record from the Late Holocene in the Turkish Highland (Middle Taurus,Turkey) - Özalp, İpek; Caner, Hülya; Karlıoğlu Kılıç, Nurgül; Avcı, Meral (Ecological Questions, 2017)
In this study, we have investigated changes of vegetation in the Mediterranean Region of Turkey approximately for the last 5000 years using pollen analysis . There were some differences in the past vegetation, but principally vegetation structure has shown similarity with the modern one. Main difference appeared with the existence of Betula.